Pengembangan Kompetensi Mahasiswa Sosiologi Pedesaan Dalam Analisis Kehidupan Masyarakat Desa Melalui Penerapan Metode Pembelajaran Inkuiri Sosial - Qomaruzzaman Azam Zami (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to determine the development of rural sociology students' competence in analyzing village community life through the application of social inquiry learning methods. The research method applied in this study is the action research method. This research is included in the applied research category which integrates knowledge, research and action. This research explains the effectiveness of social inquiry learning methods in improving the analytical competence of rural sociology students. The social inquiry method, which emphasizes active student involvement through exploration and investigation of social phenomena, has proven effective in improving students' understanding, analytical skills and critical thinking abilities. Through applying this method, students not only understand rural sociology theory but are also able to apply it in empirical analysis. The implementation of this method in the form of action research shows a significant increase in student learning outcomes from the first cycle to the second cycle. The research results show that students who are involved in the social inquiry method are able to carry out a more in-depth analysis of social phenomena in rural areas, as well as showing increased cooperation skills and courage in discussions. This conclusion is supported by observation results which show an increase in the quality of learning and the results of student self-evaluation.